Penyuluhan Kesehatan Reproduksi dan Generasi Berencana secara Daring pada Siswa SMPN 1 Sleman - Yustiana Olfah; Tri Siswati; Katri Andini Surijati (LPPM STIKES Guna Bangsa Yogyakarta, 2022)
Knowledge about reproductive health and generation planning is one of the important things for teenagers to know, during adolescence the reproductive organs are maturing and there is a high sense of curiosity so teenagers need to get the right information from the right sources. In Indonesia, the discussion about reproductive health in adolescents is still taboo, so adolescents do not get enough information. Knowledge of reproductive health and generation planning in adolescents needs attention so that adolescents can reduce risky behavior such as having premarital sex, promiscuity, and sexually transmitted diseases or HIV/AIDS. The purpose of the service is to increase knowledge about reproductive health and generation planning in SMPN 1 Sleman students, which is attended by 112 students. The strategy is carried out using online counseling which is followed up by personal consultation via WhatsApp (WA). Of the 112 students after reproductive health counseling, 83.03% experienced an increase, 6.25% experienced a decrease, while those who received a fixed/neutral score or equal to the value before counseling/pre amounted to 10.71%. Of the 112 students after the planned generation counseling, 73.21% experienced an increase, 13.39% experienced a decrease, while those who received a fixed/neutral score or equal to the value before the counseling/pretest were 15 13.39%. Knowledge of adolescents related to reproductive health and generation planning is very important so that adolescents can avoid reproductive health problems and plan better for their future.